Reflections on domestic violence during the movement control order: case study evidence from media reports - Adam Andani Mohammed; Md. Sayed Uddin; Abdallah Mpawenimana Saidi (2021)
The study investigates the incidence of domestic violence as reported by the press under the Movement Control Order MCO during the pandemic. The study also discussed how of issues of domestic violence can be handled now and during future pandemics. Empirical evidence used in this study is based on secondary data and qualitative analysis technique adopted to assess issues of domestic violence. To get relevant data, Google Scholar was used as a tool to access the major databases provided by Springer, IISTE, Tailor and Frances, Emerald, Elsevier, Sage and others. Data were obtained from newspaper articles and news articles from various online news outlets as the only source to access data of incidence of domestic violence in Malaysia during the lockdown. Results indicate a slight decrease in calls on domestic violence immediately after the MCO was implemented on March 18. It is found that the decrease was due to the fact that survivors or victims were trapped with the abusers and could not seek help or escape. The study further found that organizations attending to domestic violence cases reported a serious increase in number of abuse cases in Malaysia in the second week of the MCO thus between 18 and 31 March. The findings are intended to contribute to the narratives on violence against women now and during future disease outbreaks. It may also assist in the future improvement of the provision of services and interventions for victims of domestic violence during pandemic.